Dear People, This is Production Function and it comes from my economics book. The equation is saying that output per worker (Y/L) is equal to capital per worker (K/L) times the efficiency of labor (E) where alpha is a parameter between zero and one. The chapter is explaining the equation. I don't understand the concept (math) of how the books gets to (Y/L)1-α= (K/L)α (E)1-α after it divides both sides by (Y/L)α Thanks so much and I hope this makes sense α=alpha (superscript) 1-α=1 minus alpha (superscript) Y/L=(K/L)α (E)1-α Rewrite K/L as (K/Y) times (Y/L) Y/L=(K/Y)α (Y/L)α (E)1-α Divide both sides by (Y/L)α (Y/L)1-α= (K/L)α (E)1-α -->Please can someone help me understand how you get (Y/L)1-α I don’t understand the logic. Does it have to do with power rule?.